2017
DOI: 10.1038/eye.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of choroidal tumors with optical coherence tomography: enhanced depth imaging and OCT-angiography features

Abstract: AimTo describe the vascular features of choroidal tumors using enhanced depth imaging (EDI), optical coherence tomography (OCT), and OCT-angiography.MethodsIn this prospective study, we evaluated 116 Caucasian patients with choroidal tumors (60 eyes with choroidal nevi, 40 with choroidal melanoma, 6 with choroidal hemangioma, 2 with optic disc melanocytoma, 6 with choroidal osteoma, and 2 with retinal metastases). Patients underwent a complete ophthalmic examination including bulbar echography, EDI-OCT, OCT-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 20 publications
1
52
1
3
Order By: Relevance
“…The introduction of optical coherence tomography angiography (OCT-A) into the clinical practice allows the detection and visualization of blood flow and morphology of retinal vessels [9]. Very recently, we have demonstrated that OCT-A is a reliable, noninvasive procedure with which to evaluate the vascularization of small choroidal tumors [10]. The aim of the present study was to evaluate whether OCT-A can be used to quantify the extent of vascular changes in radiation maculopathy, and changes in the tumor vasculature in eyes treated with plaque radiotherapy for choroidal melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of optical coherence tomography angiography (OCT-A) into the clinical practice allows the detection and visualization of blood flow and morphology of retinal vessels [9]. Very recently, we have demonstrated that OCT-A is a reliable, noninvasive procedure with which to evaluate the vascularization of small choroidal tumors [10]. The aim of the present study was to evaluate whether OCT-A can be used to quantify the extent of vascular changes in radiation maculopathy, and changes in the tumor vasculature in eyes treated with plaque radiotherapy for choroidal melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced depth imaging (EDI)-OCT showed CCH as a lesion with a smooth, sloping anterior surface without choriocapillaris compression [12,14]. Other authors described CCH in EDI-OCT images as a medium-to-low reflective band with a homogeneous signal and intrinsic spaces that possibly correspond to vascular spaces [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…De nition of choroidal hemangioma (both criteria had to be met): EDI-OCT showed elevation of the retina/choroid complex with a low-to-medium re ective signal from the lesion (14) and indirect ophthalmoscope and color fundus photography showed an orange elevated tumor (15) or a difference in color of the fundus between fellow eyes. (13) ( Fig.…”
Section: Diagnosis Of Swsmentioning
confidence: 99%